KEMAMPUAN KOMUNIKASI MATEMATIS BERDASARKAN GENDER MELALUI TUTOR SEBAYA DAN CTL - Amanda Syahri Nasution; Rahmadani Rahmadani; Rosmila Pulungan (STKIP Andi Matappa, 2020)
Mathematical communication ability of collegers can differ based on the learning model applied. The peer teaching model and CTL are models that can be used as alternatives to see the differences in collegers' mathematical communication ability. The difference in the abilities of these students can not only be seen from the choice of models but also based on gender. Gender can be a benchmark for determining understanding of mathematical communication. The study intends to look at differences in understanding of collegers' mathematical communication based on gender and presence or absence a relationship of peer teaching and CTL with gender on understanding of collegers' mathematical communication. This type of research is a quasi experiment with the research sample involving two classes. The first class applies the peer teaching model while the second class applies the CTL model. The research data came from a test of collegers' mathematical communication skills. Analysis of research data in the form of descriptive analysis and inferential analysis using Two-Way ANOVA. Research proves that there are differences in collegers 'understanding of mathematical communication based on gender and there is no relationship between peer teaching and CTL with gender on collegers' understanding of mathematical communication. Male collegers are better able to communicate mathematical in written form in written text 52% and mathematical expressions 54% while female collegers are better able to communicate in drawings 55%.